Kedudukan Rasio Decidendi Hakim Dalam Pemenuhan Hak Restitusi Kepada Korban kejahatan Seksual pada Anak - Deni Setiyawan; Muhammad Ramli; Noor Rahmad (JATIJAJAR LAW REVIEW, 2022)
Children grow and develop in their lives cannot be separated from social and environmental influences in which they live and grow. We often see children who are victims of sexual crimes, especially crimes of rape. Even though protection for children has been regulated in Law Number 35 of 2014 concerning Child Protection (Child Protection Law) and Government Regulation Number 43 of 2017 concerning the Implementation of Restitution for Children Who Become Victims of Crime. However, crimes against children continue to occur and pay more attention to that the law does not explain the amount of compensation for victims of sexual crimes, in this case a child. Seeing this problem, the judge must prioritize the fulfillment of the rights of the child as a victim in his decision. Because judges have an important role in determining the rights of victims through legal analysis, (ratio decidendi). This study aims to describe the position of the Judge's Decidendi Ratio in Fulfilling the Right of Restitution to Victims of Sexual Crimes in Children. The concentration of this research discusses the position of Government Regulation Number 43 of 2017 concerning the Implementation of Restitution for Children Who Become Victims of Crime in determining the amount of restitution, then the role of the position of judges who have the right of the ratio decidendi in determining the amount of compensation for victims by prioritizing justice to victims. . This study uses a normative method with a normative juridical approach. The results obtained: first, the position of Government Regulation Number 43 of 2017 concerning the Implementation of Restitution for Children Who Become Victims of Crime in determining the amount of restitution. Second, the role of the judge who has the right of the ratio decidendi in determining the amount of compensation for the victim by prioritizing justice to the victim.